Book Review: Harber, Clive. Schooling for Peaceful Development in Post-Conflict Societies: Education for Transformation?. Springer, 2019. - Fatah, Anton Abdul (President University, 2021)
Book Review: Harber, Clive. Schooling for Peaceful Development in Post-Conflict Societies: Education for Transformation?. Springer, 2019. xiv + 306 pp. US63.70. Cham, Switzerland. ISBN 978-3-030-17688-4.